Silver nanoparticles biogenically synthesised using Maclurodendron porteri extract and their bioactivities - Badrillah, Nadhirah; Darnis, Deny Susanti; Tengku Mohd. Kamil, Tengku Karmila; Swandiny, Greesty Finotory; Widyastuti, Yuli; Zaini, Erizal; Bakhtiar, M. Taher (Elsevier Ltd., 2024)
Silver nanoparticle is widely used in various field including medical, cosmetic, food and industrial purposes due to their unique properties in electrical conductivity, thermal, and biological activities. In the medical field, silver nanoparticles (AgNPs) have been reported to have strong antimicrobial and cytotoxic activities. This study aimed to synthesize and characterize silver nanoparticles (AgNPs) using Maclurodendron porteri (MP) extract and to evaluate the antimicrobial and cytotoxic activities of the synthesised MP-AgNPs. Green method of Ultrasound Assisted Extraction (UAE) was used to extract the leaves of M. porter. Liquid Chromatography-Mass Spectrometry/Quadrupole time-of-flight (LC-MS/QTOF) was used to identify the compounds in the leaf extract of M. porteri. Characterisation of the synthesised nanoparticles involved ultraviolet–visible (UV–Vis), Fourier Transform Infrared (FTIR), scanning electromagnetic microscopy (SEM), Zeta potential Analyzer and Particle Size Analyzer. The cytotoxic assay was conducted on MCF-7 and Caco-2 cell lines by MTT assay. Antimicrobial activity was tested on Gram-negative and Gram-positive bacteria using the disc diffusion method. Based on LC-MS/QTOF analysis, 430 compounds were found. The identified major compounds consist of amino acids, polyphenols, steroids, terpenoids and heterocyclic compounds which possibly act as reducing agents. 1 mM, 5 mM and 10 mM of silver nitrate solution were mixed with the leaf extract to form silver nanoparticles. 1.2 mg/ml of MP-AgNPs were found to have antibacterial activity againstB. subtilis, S. aureus, E. coli, and P. aeruginosa with inhibitory zones of 8.0 ±0.36 mm, 8.5 ±0.45 mm, 7.5 ±0.36 mm, and 9.0 ±0.40 mm respectively. MP-AgNPs showed no cytotoxic activity against Caco-2 and MCF-7 cells. In conclusion, the presence of major amine compounds such as 10,11-dihydro-10,11-dihydroxyprotriptyline and harderoporphyrin in the extract facilitated the synthesis of AgNPs and the nanoparticle showed weak bioactivities in the assay conducted.